GLUT4 Traffic: Perspectives from Cultured Muscle Cells - JeBailey, Lellean; Randhawa, Varinder K.; Ishiki, Manabu; Klip, Amira (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
Insulin is largely responsible for the mobilization of dietary glucose in muscle and fat tissues, through exocytosis of glucose transporters from intracellular stores to the plasma membrane. Here we review the current understanding of insulin-induced translocation of GLUT4 in cultured muscle cells expressing myc-tagged GLUT4, and compare and contrast this knowledge with that obtained using adipose cells in culture. We summarize 1) The insulin signalling components required for GLUT4 traffic; 2) The steps of GLUT4 traffic susceptible to regulation by insulin signals; 3) The molecular mechanisms of GLUT4-vesicle fusion with the cell surface; and 4) The role of the actin cytoskeleton in GLUT4 translocation. The findings summarized lead to a hypothetical model for GLUT4 traffic in muscle cells where, in the basal state, GLUT4 molecules recycle to and from the plasma membrane via endosomes independently of the actin cytoskeleton. Insulin activation of phosphatidylinositol (PI) 3-kinase and Akt accelerates GLUT4 transit through endosomes en route to a specialized compartment. The newly identified Akt substrate, AS160 appears to facilitate GLUT4 exit from the specialized compartment towards the plasma membrane. In parallel, insulin regulates the actin cytoskeleton via PI3- kinase-dependent activation of the small GTPase Rac. The resulting actin remodelling is thought to facilitate the spatial segregation of insulin-dependent signals and GLUT4-rich vesicles. Finally, fusion of GLUT4 vesicles with the plasma membrane also involves PI 3-kinase-signalling and requires the v-SNARE VAMP2.
Keywords: gtpase-activating (gap) domain